Damage Detection Applied to a Full-Scale Steel Bridge Using Temporal Moments. (27th February 2020) - Svendsen, Bjørn T.; Frøseth, Gunnstein T.; Rönnquist, Anders
Abstract : The most common damages in existing highway and railway steel bridges are related to fatigue and are, as reported in the literature, found in the structural system of the bridge deck. This paper proposes a methodology for detecting damaged joint connections in existing steel bridges to improve the quality of bridge inspections. The methodology combines the use of temporal moments from response measurements with an appropriate instrumentation setup. Damaged joint connections are identified by comparing statistical parameters based on temporal moments to a baseline, where the baseline data are established from statistical parameters evaluated for all considered joint connections. Localization of damaged joint connections is performed by utilizing the instrumentation setup. The feasibility of the proposed methodology is demonstrated through an experimental study on a full-scale steel riveted truss bridge with two known damages below the bridge deck, where both damages are identified and localized. The proposed methodology can improve the identification of critical structural damage during bridge inspections and is applicable to open-deck steel bridges.